Polyurethane composition, polishing pad containing same and application of polishing pad

By using a polyurethane composition and a flocculant-enhanced polishing pad buffer layer and providing grooves thereon, the problem of poor flat scraping effect of existing polishing pads in film materials or nonwoven materials is solved, and the problem of poor smoothing pads in film materials or nonwoven materials is achieved. Higher thickness uniformity and polishing efficiency.

CN119458142APending Publication Date: 2025-02-18WANHUA CHEM GRP ELECTRONIC MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411401671.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing polishing pads have poor flat scraping effects in film materials or nonwoven materials, resulting in reduced grinding rate and low flatness, and severe thickness unevenness.

Method used

A polyurethane composition is used as the buffer layer material, a flocculant is added to enhance viscoelasticity, and grooves are provided on the buffer layer to improve uniformity of the polishing layer.

Benefits of technology

The thickness uniformity and polishing efficiency of the polishing pad are improved, and the bonding force between the polishing layer and the buffer layer is enhanced, ensuring that the thickness difference from the center to the edge is within a small range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119458142A_ABST
    Figure CN119458142A_ABST
Patent Text Reader

Abstract

The invention relates to a polyurethane composition, a polishing pad containing the composition and application of the polishing pad, the composition comprises polyurethane resin and an additive, the additive comprises a flocculating agent, and the flocculating agent comprises one or more of small molecule quaternary ammonium salt and polyquaternary ammonium salt. The polyurethane composition disclosed by the embodiment of the invention can be used for preparing a buffer layer of the polishing pad, and the viscoelasticity of the polyurethane resin can be increased in the presence of the flocculating agent, so that the prepared polishing pad has better thickness uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to chemical mechanical polishing, and in particular to a polishing pad with higher thickness uniformity and polishing efficiency. Background Art

[0002] Chemical Mechanical Polishing (CMP) is a process that combines the grinding action of nanoparticles with the chemical corrosion of polishing liquid to flatten the workpiece being polished on the polishing pad. The polishing pad is one of the important consumables that determines the polishing rate and flattening ability in the CMP process. The surface of the polishing pad has a fiberboard structure with many follicle holes, which plays a role in storing and transporting polishing liquid, removing processing residual materials, transferring mechanical loads and maintaining the polishing environment in the CMP process. Therefore, the polishing pad used for CMP must have good chemical stability (corrosion resistance), hydrophilicity and mechanical properties. CMP can remove excess materials and impurities on the surface and reduce defects such as surface roughness and scratches. The polishing quality of each layer of silicon wafer (i.e., the degree of surface flattening) directly determines the quality of semiconductor chips.

[0003] Soft polyurethane polishing pads are usually used for fine polishing or final polishing to achieve a lower defect rate for polishing materials. However, existing polishing pads either cannot meet the requirements of flat scraping in film materials or non-woven materials, which will cause the overall polishing rate of the polishing pad to decrease and the flatness to decrease; or the surface roughness of the polishing pad buffer layer is low, which cannot meet the overall uniformity of the polishing pad, resulting in uneven thickness from the middle to the edge of the polishing pad, resulting in a lower overall flatness of the polishing pad.

[0004] From the actual usage, the high overall uniformity of the soft polishing pad can increase the contact area between the polishing material and the polishing pad. Therefore, improving the uniformity of the soft polishing pad is of great significance. Summary of the invention

[0005] In order to overcome at least one defect of the above-mentioned prior art, in the first aspect, an embodiment of the present invention provides a polyurethane composition, including a polyurethane resin and an additive, wherein the additive includes a flocculant, and the flocculant includes one or more of a small molecule quaternary ammonium salt and a polyquaternary ammonium salt.

[0006] In a second aspect, an embodiment of the present invention provides a polishing pad, comprising a buffer layer and a polishing layer, wherein the buffer layer is made from the above-mentioned polyurethane composition.

[0007] In a third aspect, an embodiment of the present invention provides a method for preparing the above-mentioned polishing pad, comprising the following steps:

[0008] providing the buffer layer;

[0009] The polishing layer slurry is coated on the buffer layer to form the polishing layer.

[0010] In a fourth aspect, an embodiment of the present invention provides use of the above-mentioned polishing pad in chemical mechanical polishing.

[0011] The polyurethane composition according to one embodiment of the present invention can be used to prepare a buffer layer of a polishing pad. The presence of the flocculant can increase the viscoelasticity of the polyurethane resin, thereby making the prepared polishing pad have better thickness uniformity. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] The accompanying drawings are only used to illustrate specific embodiments and are not to be considered as limiting the present invention.

[0013] Figure 1 is a cross-sectional view of a polishing pad according to an embodiment of the present invention;

[0014] Figure 2 A top view of a buffer layer according to an embodiment of the present invention;

[0015] The following are the descriptions of the reference numerals:

[0016] 10. Buffer layer; 11. Groove; 12. Central area; 20. Polishing layer; 21. Protruding structure. DETAILED DESCRIPTION

[0017] Typical embodiments that embody the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various changes in different embodiments without departing from the scope of the present invention, and the descriptions therein are essentially used as illustrations rather than to limit the present invention.

[0018] An embodiment of the present invention provides a polyurethane composition, including a polyurethane resin and an additive, wherein the additive includes a flocculant, and the flocculant includes one or more of a small molecule quaternary ammonium salt and a polyquaternary ammonium salt.

[0019] In one embodiment, the flocculant includes one or more of benzalkonium chloride, dimethyldiallylammonium chloride homopolymer (DMDAAC, polyquaternium-6), and 2-hydroxy-3-(trimethylamino)propyl polyethylene oxide cellulose chloride ether (JR-400, polyquaternium-10).

[0020] In one embodiment, based on the mass of the polyurethane resin, the mass content of the flocculant in the polyurethane composition can be 0.1-1%, and further can be 0.1-0.4%, for example 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 0.9%.

[0021] In one embodiment, the additive further includes a thickener, which may include one or more of polyethylene oxide (PEO), polyether-modified polysilane grafted with polyether and polydimethylsiloxane, a blend of acrylate and polydimethylsiloxane, associative swelling acrylate (e.g., TT-615), and grafted hydroxyethyl cellulose.

[0022] In one embodiment, the thickener includes a waterborne polyurethane, a blend of acrylates and dimethicone, and dodecanol.

[0023] In one embodiment, based on the mass of the polyurethane resin, the mass content of the thickener in the polyurethane composition can be 0.1-2%, and can further be 0.5-1%, for example, 0.2%, 0.3%, 0.5%, 0.8%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%.

[0024] In one embodiment, the additive further includes a nonionic surfactant, and the nonionic surfactant may include one or more of polyoxyethylene sorbitan monooleate (Tween-80), polyoxyethylene sorbitan palmitate (Tween-40), polyethylene glycol monooleate, polyethylene glycol monostearate, sorbitan tristearate, and sorbitan monooleate; wherein the polyethylene glycol in polyethylene glycol monooleate and polyethylene glycol monostearate may be polyethylene glycol 400.

[0025] In one embodiment, based on the mass of the polyurethane resin, the mass content of the nonionic surfactant in the polyurethane composition can be 2-4%, and can further be 2-3%, for example, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.8%.

[0026] In one embodiment, the additive further includes a solvent, and the solvent may include one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0027] In one embodiment, based on the mass of the polyurethane resin, the mass content of the solvent in the polyurethane composition may be 40-50%, for example, 42%, 45%, or 48%.

[0028] In one embodiment, the polyurethane resin may be a solvent-based polyurethane resin, preferably a wet-process polyurethane resin, which is a common synthetic leather resin. Further, the 100% modulus of the solvent-based polyurethane resin may be 3 to 10 MPa, and further may be 5 to 8 MPa, such as 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa. Among them, the 100% modulus may also be referred to as 100% mold or 100% modulus.

[0029] In one embodiment, the polyurethane resin is a wet-process polyurethane resin for leather, and its solid content may be 30%, for example, it may be HDW-1151EB produced by Shanghai Huide Technology.

[0030] In one embodiment, the polyurethane composition includes 100 parts by mass of a polyurethane resin, 0.1 to 1 parts by mass of a flocculant, 0.1 to 2 parts by mass of a thickener, 2 to 4 parts by mass of a nonionic surfactant, and 40 to 50 parts by mass of a solvent.

[0031] Reference Figure 1 As shown, one embodiment of the present invention provides a polishing pad, comprising a buffer layer 10 and a polishing layer 20, wherein the buffer layer 10 is made of the above-mentioned polyurethane composition.

[0032] In one embodiment, referring to Figure 2 As shown, one or more grooves 11 (or slots) are provided on the buffer layer 10 .

[0033] In one embodiment, the buffer layer 10 and the polishing layer 20 are both circular.

[0034] In one embodiment, the buffer layer 10 includes a first surface and a second surface that are opposite to each other, one or more grooves 11 are disposed on the first surface, and the buffer layer 10 is connected to the polishing layer 20 through the first surface.

[0035] In one embodiment, the polishing layer 20 is disposed on the first surface of the buffer layer 10 having the groove 11 , and the protruding structure 21 thereof is disposed in (or embedded in) the groove 11 of the buffer layer 10 .

[0036] In one embodiment, the protruding structure 21 of the polishing layer 20 matches (or corresponds to) the structure of the recessed structure 11 of the buffer layer 10 .

[0037] In one embodiment, the cross-section of one or more grooves 11 disposed on the buffer layer 10 may be in the shape of one or more of a curve, a straight line, a circle, a ring, a fan, a spiral, a rectangle, a trapezoid, a triangle, a hexagon, a fractal shape, and a grid. Further, the buffer layer 10 may include grooves 11 of one or more shapes. The cross-section refers to a cross-section parallel to the buffer layer 10 or a cross-section perpendicular to the thickness direction of the buffer layer 10.

[0038] In one embodiment, the grooves 11 of the buffer layer 10 may be one or more of curved grooves, linear grooves, circular grooves, and a combination thereof.

[0039] In one embodiment, the grooves 11 on the buffer layer 10 may be a plurality of circular grooves (ie, circular holes) arranged at intervals.

[0040] In one embodiment, the cross section of one or more grooves 11 disposed on the buffer layer 10 is annular (or circular), and correspondingly, the protruding structure 21 of the polishing layer 20 is a circular ring.

[0041] In one embodiment, the width of one or more grooves 11 can be 0.1-10 mm, further can be 0.2-8 mm, and further can be 0.5-5 mm, such as 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm. For example, the groove 11 is a concentric annular groove, and its width is the difference between the outer diameter and the inner diameter divided by 2.

[0042] In one embodiment, the depth of one or more grooves 11 may be 0.1-1 mm, further 0.2-0.8 mm, further 0.3-0.6 mm, for example 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 10 mm.

[0043] In one embodiment, the depths of the plurality of grooves 11 are the same or different. Further, the plurality of grooves 11 may be annular grooves having the same center line, and the depths of the grooves 11 increase or decrease successively from the outermost groove 11 to the innermost groove 11, so as to increase the contact area between the polishing layer 20 and the buffer layer 10. The outermost groove 11 refers to the groove 11 farthest from the center line of the annular groove, and the innermost groove 11 refers to the groove 11 closest to the center line.

[0044] In one embodiment, the plurality of annular grooves 11 have the same center line, which are concentric grooves 11. Furthermore, the distance between two adjacent concentric grooves 11 (i.e., the distance between the outer ring of the inner groove and the inner ring of the outer groove) can be 1 to 10 mm, for example, 2 mm, 3 mm, 5 mm, 6 mm, 8 mm.

[0045] In one embodiment, a plurality of concentric annular grooves 11 are provided on the buffer layer 10, and the depths of the plurality of annular grooves 11 decrease from the outside to the inside, and the decreasing amplitude may be 0.01-1 mm, further 0.02-0.8 mm, and further 0.03-0.1 mm, for example 0.01 mm, 0.02 mm, 0.03 mm, 0.04 mm, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm. That is, the annular groove 11 with the largest radius located at the outermost side has the largest depth, and the annular groove 11 with the smallest radius located at the innermost side has the smallest depth.

[0046] In one embodiment, the number of grooves 11 provided on the buffer layer 10 may be 1 to 10, further may be 2 to 8, further may be 3 to 6, for example 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10.

[0047] In one embodiment, the distance between the groove 11 and the edge of the buffer layer 10 (or the edge of the polishing pad) is 10 to 700 mm, further 10 to 100 mm, further 20 to 80 mm, and further 30 to 60 mm, for example 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 90 mm, 100 mm. The groove 11 is adjacent to the edge of the buffer layer 10, so that in the subsequent process of preparing the polishing layer 20 on the buffer layer 10 by a coating process, it is more conducive to scraping the thicker edge area into the groove 11 during scraping, thereby facilitating the uniformity of the thickness of the polishing pad (or polishing layer).

[0048] In one embodiment, the buffer layer 10 (or polishing pad) is circular, and the plurality of grooves 11 are arranged radially along the surface of the buffer layer 10. For example, the plurality of grooves 11 are concentric rings with different radii, and the plurality of circular grooves 11 are arranged sequentially along the radial direction of the concentric circles or the radial direction of the buffer layer 10.

[0049] In one embodiment, the plurality of grooves 11 on the buffer layer 10 are concentric rings, and the area surrounded by the groove 11 with the smallest ring size or the innermost groove 11 (i.e., the groove 11 closest to the center of the buffer layer 10) is the central area 12. Further, the plurality of grooves 11 are ring grooves, the central area 12 is circular, and the inner diameter of the groove 11 closest to the center of the buffer layer 10 is equal to the diameter of the central area 12. Further, the buffer layer 10 may be circular, and its diameter may be, for example, 800 to 1000 mm, and the diameter of the central area 12 may be 250 to 320 mm (e.g., 280 mm, 300 mm, 310 mm), and the distance between the groove 11 farthest from the center of the buffer layer 10 (located at the outermost) and the edge of the buffer layer may be 72.5 to 232.5 mm; the width of the groove 11 may be 0.5 to 5 mm, and the depth may be 0.3 to 0.6 mm; and the spacing between the plurality of grooves may be 1 to 10 mm.

[0050] In one embodiment, the thickness of the buffer layer 10 can be 0.1-50 mm, further can be 0.5-2 mm, further can be 0.6-1.8 mm, and further can be 1.0-1.5 mm, for example, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, 5.0 mm, 10 mm, 15 mm, 20 mm, 30 mm, and 40 mm.

[0051] In one embodiment, the air permeability of the buffer layer 10 may be 1.50 to 2.00 cc / cm 2 / sec, and can further be 1.60 to 1.90 cc / cm 2 / sec, for example 1.50cc / cm 2 / sec、1.55cc / cm 2 / sec、1.60cc / cm 2 / sec、1.65cc / cm 2 / sec、1.70cc / cm 2 / sec、1.75cc / cm 2 / sec、1.80cc / cm 2 / sec、1.85cc / cm 2 / sec、1.90cc / cm 2 / sec、1.95cc / cm 2 / sec、2.00cc / cm 2 / sec.

[0052] In one embodiment, the hardness of the buffer layer 10 is higher than that of the polishing layer 20, so that it can provide a hard buffering effect during the polishing process, thereby ensuring that the polishing layer 20 is not easily deformed.

[0053] In one embodiment, the hardness of the buffer layer 10 is 30-60 DO (Shore DO), and may further be 40-50 DO, for example, 30 DO, 35 DO, 40 DO, 45 DO, 50 DO, 55 DO, and 60 DO.

[0054] In one embodiment, the hardness of the polishing layer 20 is 10-60A (Shore hardness), and can further be 20-30A, for example, 20A, 21A, 22A, 23A, 25A, 28A, 30A, 40A, and 50A.

[0055] In one embodiment, the density of the buffer layer 10 is 0.1-0.5 g / cm 3 , for example 0.2g / cm 3 , 0.3g / cm 3 , 0.4g / cm 3 .

[0056] In one embodiment, the polishing pad includes a polishing layer 20 , a first adhesive layer, and a buffer layer 10 which are arranged in sequence, wherein the first adhesive layer is used to connect the polishing layer 20 and the buffer layer 10 together.

[0057] In one embodiment, the polishing pad includes a polishing layer 20, a buffer layer 10, and a release layer which are sequentially arranged.

[0058] In one embodiment, the polishing pad includes a polishing layer 20, a buffer layer 10, a second adhesive layer and a release layer which are arranged in sequence, wherein the second adhesive layer is used to connect the buffer layer 10 and the release layer together.

[0059] In one embodiment, the polishing pad includes a polishing layer 20, a first adhesive layer, a buffer layer 10, a second adhesive layer and a release layer which are arranged in sequence.

[0060] In one embodiment, the first adhesive layer and / or the second adhesive layer may be a hot melt adhesive layer or a pressure sensitive adhesive layer.

[0061] In one embodiment, the polishing pad is circular in shape.

[0062] One embodiment of the present invention provides a method for preparing the above-mentioned polishing pad, comprising the following steps:

[0063] Providing a buffer layer 10;

[0064] The polishing layer slurry is coated on the buffer layer 10 to form the polishing layer 20 .

[0065] In one embodiment, during the preparation of the polishing layer 20, as the polishing layer slurry is applied, the grooves 11 on the buffer layer 10 can act as a reservoir, and when the edge is scraped too thick, the coating can be scraped into the surface grooves 11 to improve the surface uniformity of the polishing layer 20 and the polishing pad, so that the difference in thickness from the center to the edge of the polishing pad is kept within a small range. Further, the difference in thickness from the center to the edge of the polishing pad is 0.01 to 0.2 mm, and can further be 0.01 to 0.1 mm, such as 0.01 mm, 0.02 mm, 0.03 mm, 0.04 mm, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm, 0.1 mm.

[0066] In one embodiment, during the preparation of the polishing layer 20, part of the polishing layer slurry enters the groove 11 of the buffer layer, so that part of the structure of the polishing layer 20 (i.e., the protruding structure 21 mentioned above) after curing is embedded in the buffer layer, thereby increasing the bonding force between the two. Furthermore, the protruding structure 21 embedded in the buffer layer 10 corresponds to the shape of the groove 11.

[0067] In one embodiment, the buffer layer or the polishing layer is prepared by a condensation film forming method.

[0068] In one embodiment, the components of the polyurethane composition are mixed to prepare polyurethane slurry; the polyurethane slurry is applied to a non-woven fabric, and then the slurry is solidified and separated from the non-woven fabric to prepare a buffer sheet (or buffer film).

[0069] In one embodiment, the polyurethane slurry can be applied to a non-woven fabric with a thickness of 0.3 to 0.4 mm, and the non-woven fabric coated with the slurry is placed in a first coagulation bath containing 5 to 10% N,N-dimethylformamide for curing for 10 to 20 minutes. After the non-woven fabric is separated from the cured structure, the cured structure is placed in an oven at 100° C. and dried for 10 to 30 minutes to obtain a buffer sheet.

[0070] In one embodiment, one or more grooves 11 may be formed on the buffer sheet by grinding or laser processing.

[0071] In one embodiment, the prepared buffer sheet is punched into a circular sheet, and its surface is engraved by a notcher / milling machine to form one or more grooves 11 .

[0072] In one embodiment, the polishing layer slurry includes 100 parts by mass of a polyurethane resin, 0.1 to 1 parts by mass (e.g., 0.3 parts by mass, 0.4 parts by mass, 0.5 parts by mass) of a non-ionic surfactant and 50 to 80 parts by mass (e.g., 60 parts by mass, 65 parts by mass, 70 parts by mass) of a solvent, wherein the types of the polyurethane resin, the non-ionic surfactant and the solvent are suitable for the types of corresponding materials of the above-mentioned polyurethane composition for preparing the buffer layer.

[0073] In one embodiment, the polishing layer slurry includes 100 parts by mass of a polyurethane resin, 0.2 to 0.8 parts by mass of a nonionic surfactant, and 55 to 75 parts by mass of a solvent.

[0074] In one embodiment, in the polishing layer slurry, the mass ratio of the polyurethane resin, the nonionic surfactant, and the solvent may be 100:0.1-1:50-80, for example, 100:0.5:50, 100:0.8:52, or 100:0.3:55.

[0075] In one embodiment, the polishing layer slurry is coated on a buffer sheet (or buffer layer) provided with a groove 11 with a thickness of 1 to 1.5 mm, and then the buffer sheet is placed in an oven at 50 to 80° C. for 1 to 10 minutes, then immersed in N,N-dimethylformamide for curing for 10 to 60 minutes, and then placed in an oven at 50 to 150° C. for 10 to 60 minutes.

[0076] In one embodiment, the above steps obtain a polishing layer / buffer layer structure, and the above structure is pressed and affixed with a backing adhesive using existing steps, and a release layer is affixed to obtain a polishing pad.

[0077] An embodiment of the present invention provides the use of the polishing pad in chemical mechanical polishing. Further, the use of the polishing pad for polishing can achieve a better polishing rate and high flatness of the polishing element (such as a wafer).

[0078] In one embodiment, the polishing pad can be used for chemical mechanical polishing (or chemical mechanical planarization) of components such as magnetic substrates, optical substrates or semiconductor substrates, for example, for chemical mechanical polishing of copper wafers, silicon wafers or wafers.

[0079] In one embodiment, the polishing method comprises the following steps:

[0080] Providing the aforementioned polishing pad;

[0081] Applying a pressure to the polishing element to press against the polishing pad;

[0082] Relative motion is provided to the polishing element and the polishing pad to perform polishing.

[0083] The polyurethane composition of one embodiment of the present invention can be used to prepare a buffer layer of a polishing pad. The presence of a flocculant can increase the viscoelasticity of the polyurethane resin, thereby reducing or eliminating peeling and damage during the scraping process of preparing the buffer layer, thereby making the buffer layer have better flatness.

[0084] The polyurethane composition of one embodiment of the present invention can be used to prepare a buffer layer of a polishing pad, wherein the presence of a thickener is beneficial to reducing surface tension, increasing the hardness of the buffer layer, and enabling the prepared buffer layer to have better flatness.

[0085] A polishing pad or a preparation method thereof according to an embodiment of the present invention can allow excess polishing layer slurry at the edge to flow into the groove 11 by setting a groove 11 on the buffer layer, thereby improving the overall uniformity of the polishing pad and facilitating a higher polishing rate and flattening of the polishing element during the polishing process.

[0086] A polishing pad according to an embodiment of the present invention can increase the friction area between the buffer layer and the polishing layer slurry by setting grooves on the buffer layer, so that the slurry is better distributed throughout the buffer layer and continuously stacked, thereby greatly improving the thickness uniformity of the polishing pad from the center to the edge.

[0087] A polishing pad according to an embodiment of the present invention can improve the surface flatness of a polishing element by being used for chemical mechanical polishing.

[0088] The preparation of a polishing pad according to an embodiment of the present invention is further described below in conjunction with the accompanying drawings and specific examples. The raw materials and test methods involved in each example are as follows.

[0089] raw material

[0090] 1. Polyurethane resin HDW-3030 (100% modulus 3MPa), Huada Chemical;

[0091] 2. Polyurethane resin HDW-3050 (100% modulus 5MPa), Huada Chemical;

[0092] 3. N,N-dimethylformamide, analytical grade, Komiou;

[0093] 4. Sorbitan monooleate, analytical grade, Aladdin;

[0094] 5. Homopolymer of dimethyldiallylammonium chloride (polyquaternium 6), Merrill Chemical.

[0095] Test Method

[0096] 1. Testing of removal rate and non-uniformity

[0097] The film thickness was tested using an AMBioS XP-300 step profiler. The average value of the film thickness at 9 points was taken. The removal rate of the copper target was determined based on the difference before and after CMP. and non-uniformity % (NU%).

[0098] 2. Hardness test of polishing layer

[0099] The Shore A hardness (test standard JIS K 6253) is used to obtain the hardness value by measuring the depth of the indenter pressed toward the surface of the test piece by a spring.

[0100] 3. Test of elongation at break of buffer layer

[0101] Use a universal material testing machine to fix the sample between two constant clamps, apply a force of 50N at a constant speed of 100mm / min, and gradually increase it until the sample breaks. Determine the elongation at break based on the tensile test curve.

[0102] 4. Hardness test of buffer layer

[0103] The Shore hardness DO is used to determine the depth that can be measured by the indenter pressed against the surface of the test piece by a spring.

[0104] 5. Compression rate test of buffer layer

[0105] A universal material testing machine (Shimadzu, Japan) with a pressure head of 10 cm was used to measure the thickness t0 after an initial load of 0.5 kPa and pressurization for 30 s. Then, the thickness t1 was measured after a final pressure of 50 kPa and pressurization for 30 s. After removing all loads, the compression rate (%) = 100×(t0-t1) / t1.

[0106] 6. Thickness test

[0107] Use a micrometer to measure the thickness of a diameter at 9 points, with each test point being -375mm, -280mm, -188mm, -94mm, 0, 94mm, 188mm, 280mm, and 375mm from the center.

[0108] Preparation Example 1

[0109] Take 1 part by mass of waterborne polyurethane WO2947, add sodium hydroxide to a pH value of 8 to 9, and then slowly add water, a blend of acrylate and polydimethylsiloxane, and dodecanol into the above system in a mass ratio of 1:4:0.2 to obtain a thickener Wansei 8746.

[0110] Example 1

[0111] Preparation of buffer layer

[0112] 100 parts by mass of solvent-based polyurethane resin, 2 parts by mass of nonionic surfactant Tween-80, 0.5 parts by mass of thickener Wansei 8746, 0.2 parts by mass of flocculant polyquaternium salt 6, and 45 parts by mass of solvent N,N-dimethylformamide are prepared into polyurethane slurry; the slurry is coated on a non-woven fabric with a thickness of 0.36 mm, and immersed in a first coagulation bath containing 8wt% of N,N-dimethylformamide for curing for 12 minutes. After the non-woven fabric is separated, the remaining structure is placed in an oven at 100°C and dried for 20 minutes to obtain a buffer sheet.

[0113] Reference Figure 2 As shown, the buffer sheet is punched into a circular sheet with a diameter of 880 mm, and the first surface thereof is engraved by a notcher / milling machine to obtain three concentric annular grooves 11; the diameter of the central area 12 is 300 mm, the width of the groove 11 is 0.8 mm, the interval between adjacent grooves 11 is 2 mm, the depth of the outermost groove 11 is 0.5 mm, and the depth of the groove 11 decreases by 0.05 mm from the outside to the inside. The second surface of the buffer sheet is then ground to a thickness of 1.2 mm to obtain a buffer layer.

[0114] Preparation of polishing layer

[0115] 100 parts by mass of HDW-3030 polyurethane resin, 0.5 parts by mass of sorbitan monooleate, and 65 parts by mass of N,N-dimethylformamide were prepared into a polishing layer slurry, and the slurry was coated on the first surface of the buffer layer with a thickness of 1.2 mm; then, the buffer layer coated with the slurry was placed in an oven at 60° C. for drying for 5 minutes, then immersed in N,N-dimethylformamide for curing for 25 minutes, and then placed in an oven at 100° C. for drying for 30 minutes to obtain a polishing pad.

[0116] Example 2

[0117] Preparation of buffer layer

[0118] 100 parts by mass of solvent-based polyurethane resin, 2 parts by mass of nonionic surfactant Tween-80, 0.8 parts by mass of thickener Wansei 8746, 0.3 parts by mass of flocculant polyquaternium salt 6, and 48 parts by mass of solvent N,N-dimethylformamide are prepared into polyurethane slurry; the slurry is coated on a non-woven fabric with a thickness of 0.36 mm, and the non-woven fabric is immersed in a first coagulation bath containing 7wt% of N,N-dimethylformamide for curing for 15 minutes. After the non-woven fabric is separated, the remaining structure is placed in an oven at 100°C and dried for 20 minutes to obtain a buffer sheet.

[0119] Reference Figure 2As shown, the buffer sheet is punched into a circular sheet with a diameter of 880 mm, and the first surface thereof is engraved by a notcher / milling machine to obtain 5 concentric annular grooves 11; the diameter of the central area 12 is 280 mm, the width of the groove 11 is 0.6 mm, the interval between adjacent grooves 11 is 3 mm, the depth of the outermost groove 11 is 0.6 mm, and the depth of the groove 11 decreases by 0.04 mm from the outside to the inside. The second surface of the buffer sheet is then ground to a thickness of 1.28 mm to obtain a buffer layer.

[0120] Preparation of polishing layer

[0121] 100 parts by mass of HDW-3050 polyurethane resin, 0.4 parts by mass of sorbitan monooleate, and 70 parts by mass of N,N-dimethylformamide were prepared into a polishing layer slurry, and the slurry was coated on the first surface of the buffer layer with a thickness of 1.3 mm; then, the buffer layer coated with the slurry was placed in an oven at 60° C. for drying for 6 minutes, then immersed in N,N-dimethylformamide for curing for 30 minutes, and then placed in an oven at 100° C. for drying for 25 minutes to obtain a polishing pad.

[0122] Example 3

[0123] Preparation of buffer layer

[0124] 100 parts by mass of solvent-based polyurethane resin, 2 parts by mass of nonionic surfactant Tween-80, 0.8 parts by mass of thickener Wansei 8746, 0.3 parts by mass of flocculant polyquaternium salt 6, and 48 parts by mass of solvent N,N-dimethylformamide are prepared into polyurethane slurry; the slurry is coated on a non-woven fabric with a thickness of 0.36 mm, and the non-woven fabric is immersed in a first coagulation bath containing 7wt% of N,N-dimethylformamide for curing for 15 minutes. After the non-woven fabric is separated, the remaining structure is placed in an oven at 100°C and dried for 20 minutes to obtain a buffer sheet.

[0125] Reference Figure 2 As shown, the buffer sheet is punched into a circular sheet with a diameter of 1000 mm, and the first surface thereof is engraved by a notcher / milling machine to obtain four concentric annular grooves 11; the diameter of the central area 12 is 310 mm, the width of the groove 11 is 0.5 mm, the interval between adjacent grooves 11 is 1 mm, the depth of the outermost groove 11 is 0.5 mm, and the depth of the groove 11 decreases by 0.03 mm from the outside to the inside. The second surface of the buffer sheet is then ground to a thickness of 1.1 mm to obtain a buffer layer.

[0126] Preparation of polishing layer

[0127] 100 parts by mass of HDW-3050 polyurethane resin, 0.3 parts by mass of sorbitan monooleate, and 60 parts by mass of N,N-dimethylformamide were prepared into a polishing layer slurry, and the slurry was coated on the first surface of the buffer layer with a thickness of 1.3 mm; then, the buffer layer coated with the slurry was placed in an oven at 50°C for drying for 6 minutes, then immersed in N,N-dimethylformamide for curing for 42 minutes, and then placed in an oven at 100°C for drying for 28 minutes to obtain a polishing pad.

[0128] Example 4

[0129] Preparation of buffer layer

[0130] 100 parts by mass of solvent-based polyurethane resin, 2 parts by mass of nonionic surfactant Tween-80, 0.5 parts by mass of thickener Wansei 8746, 0.4 parts by mass of flocculant polyquaternium salt 6, and 45 parts by mass of solvent N,N-dimethylformamide are prepared into polyurethane slurry; the slurry is coated on a non-woven fabric with a thickness of 0.36 mm, and immersed in a first coagulation bath containing 8wt% of N,N-dimethylformamide for curing for 12 minutes. After the non-woven fabric is separated, the remaining structure is placed in an oven at 100°C and dried for 20 minutes to obtain a buffer sheet.

[0131] Reference Figure 2 As shown, the buffer sheet is punched into a circular sheet with a diameter of 1000 mm, and the first surface thereof is engraved by a notcher / milling machine to obtain two concentric annular grooves 11; the diameter of the central area 12 is 300 mm, the width of the groove 11 is 0.5 mm, the interval between adjacent grooves 11 is 2 mm, the depth of the outermost groove 11 is 0.5 mm, and the depth of the groove 11 decreases by 0.1 mm from the outside to the inside. The second surface of the buffer sheet is then ground to a thickness of 1.3 mm to obtain a buffer layer.

[0132] Preparation of polishing layer

[0133] 100 parts by mass of HDW-3030 polyurethane resin, 0.3 parts by mass of sorbitan monooleate, and 55 parts by mass of N,N-dimethylformamide were prepared into a polishing layer slurry, and the slurry was coated on the first surface of the buffer layer with a thickness of 1.3 mm; then, the buffer layer coated with the slurry was placed in an oven at 60°C for drying for 7 minutes, then immersed in N,N-dimethylformamide for curing for 35 minutes, and then placed in an oven at 100°C for drying for 30 minutes to obtain a polishing pad.

[0134] Comparative Example 1

[0135] This example uses the same raw materials and process as Example 1 to prepare the polishing pad, with the only difference being that no flocculant is added to the polyurethane slurry for preparing the buffer layer.

[0136] Comparative Example 2

[0137] This example uses the same raw materials and process as Example 1 to prepare the polishing pad, with the only difference being that the buffer sheet is not grooved, that is, the first surface of the buffer layer of the polishing pad does not contain the groove 11.

[0138] Comparative Example 3

[0139] The existing polyurethane polishing pad H804 produced by FUJIMI Co., Ltd. and having a non-woven fabric buffer layer was used as the polishing pad of Comparative Example 4.

[0140] According to the aforementioned method, the polishing pads prepared in the embodiments and comparative examples were subjected to relevant tests. The specific results are shown in Tables 1 and 2.

[0141] Table 1 The thickness of the polishing pads of the embodiments and comparative examples (in mm)

[0142]

[0143] Table 2

[0144]

[0145]

[0146] The polishing pads prepared in the embodiments and comparative examples were subjected to polishing tests. The polishing machine used was Huahai Qingke U300 polishing machine. The polishing process (oxidation layer polishing) parameters were: polishing pressure 1.5 psi, polishing speed 50-60 rpm, polishing liquid flow 300 mL / min, polishing time 60 s. The polished devices were subjected to relevant tests according to the above method. The results are shown in Table 3.

[0147] Table 3

[0148]

[0149] The only difference between Example 1 and Comparative Example 1 is that no flocculant is added to the slurry for preparing the buffer layer of Comparative Example 1. According to Tables 1 to 3, the thickness difference of the polishing pad prepared in Example 1 at different positions is kept below 0.02 mm, while the thickness difference of the polishing pad of Comparative Example 1 at different positions is below 0.36 mm; at the same time, the elongation at break of the buffer layer of Example 1 is 79%, which is significantly higher than the elongation at break of Comparative Example 1, which is 44%; the removal rate of Example 1 is Significantly higher removal rate than that of Comparative Example 1 The non-uniformity of Example 1 is 5.44%, which is significantly lower than the non-uniformity of Comparative Example 1, which is 13.55%. According to the above results, it can be seen that the thickness uniformity and elongation at break of the buffer layer of the polishing pad of Example 1 are significantly higher than those of Comparative Example 1, the polishing speed is significantly higher than that of Comparative Example 1, and the grinding flatness of the polished element is significantly higher than that of Comparative Example 1.

[0150] Meanwhile, the thickness uniformity, elongation at break of the buffer layer, removal rate, non-uniformity, etc. of the polishing pads of Examples 2 to 4 are maintained at similar levels to those of Example 1. Therefore, by adding a flocculant to the preparation of the buffer layer of the polishing pad, the thickness uniformity and elongation at break of the buffer layer of the polishing pad can be significantly improved, and the polishing rate and the grinding flatness of the element can also be improved.

[0151] The buffer layer of the polishing pad in Comparative Example 2 is not provided with grooves. During the scraping process of the polishing layer slurry, the edge area is thicker than the middle area due to the scraping technique. The data in Table 1 show that the error of the overall thickness of the polishing pad is greater than 0.05 mm, and the thickness difference at different positions can reach 0.28 mm, so that the edge has a greater ability to store polishing liquid than the center, thereby reducing the overall polishing rate, and the non-uniformity of the polished element is higher and the flatness is lower. At the same time, the elongation at break, removal rate, non-uniformity, etc. of the buffer layer of the polishing pad of Comparative Example 2 are all worse than those of the polishing pad of Example 1.

[0152] Comparative Example 3 is a chemical mechanical polishing pad commonly used on the market. Compared with the polishing pad of the embodiment, its compression rate is lower and its hardness is higher. Although its polishing rate (removal rate) is higher, the high hardness causes the grinding flatness to be seriously affected, resulting in a decrease in the yield rate.

[0153] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.

[0154] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.

Claims

1. A polyurethane composition comprising a polyurethane resin and an additive, wherein the additive comprises a flocculant, and the flocculant comprises one or more of a small molecule quaternary ammonium salt and a polyquaternary ammonium salt.

2. The composition according to claim 1, wherein The flocculant includes one or more of benzalkonium chloride, dimethyldiallylammonium chloride homopolymer, and chlorinated-2-hydroxy-3-(trimethylamino)propyl polyethylene oxide cellulose ether; and / or, Based on the mass of the polyurethane resin, the mass content of the flocculant is 0.1-1%; and / or, The additives also include thickeners, nonionic surfactants and solvents.

3. The composition according to claim 2, wherein Based on the mass of the polyurethane resin, the mass content of the thickener is 0.1-2%; and / or, Based on the mass of the polyurethane resin, the mass content of the nonionic surfactant is 2-4%; and / or, The thickener includes one or more of polyethylene oxide, polyether-modified polysilane grafted with polyether and polydimethylsiloxane, a blend of acrylate and polydimethylsiloxane, associative swelling acrylate, and grafted hydroxyethyl cellulose; and / or, The nonionic surfactant includes one or more of polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan palmitate, polyethylene glycol monooleate, polyethylene glycol monostearate, sorbitan tristearate, and sorbitan monooleate; and / or, The solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

4. A polishing pad comprising a buffer layer and a polishing layer, wherein: The buffer layer is made from the polyurethane composition according to any one of claims 1 to 3.

5. The polishing pad according to claim 4, wherein: The buffer layer has a higher hardness than the polishing layer; and / or, One or more grooves are provided on the buffer layer; and / or, The thickness of the buffer layer is 0.5 to 2 mm; and / or, The hardness of the buffer layer is 30-60DO; and / or, The polishing pad includes the polishing layer, the buffer layer, the second adhesive layer and the release layer which are arranged in sequence.

6. The polishing pad according to claim 5, wherein: The cross-section of the one or more grooves is selected from one or more of a curve, a straight line, a circle, a ring, a fan, a spiral, a rectangle, a trapezoid, a triangle, a hexagon, a fractal shape, and a grid; and / or, The width of the one or more grooves is 0.1 to 10 mm; and / or, The depth of the one or more grooves is 0.1 to 1 mm; and / or, The number of the grooves is 1 to 10; and / or, A plurality of annular grooves having the same center line are arranged on the buffer layer.

7. The polishing pad according to claim 5, wherein: The cross section of the one or more grooves is circular; and / or, The width of the one or more grooves is 0.2 to 8 mm; and / or, The depth of the one or more grooves is 0.2 to 0.8 mm; and / or, The hardness of the polishing layer is 10-60A.

8. The polishing pad according to claim 5, wherein: The width of the one or more grooves is 0.5 to 5 mm; and / or, The depth of the one or more grooves is 0.3 to 0.6 mm; and / or, A plurality of concentric annular grooves are arranged on the buffer layer, and the depths of the plurality of annular grooves decrease from the outside to the inside, with a decreasing amplitude of 0.01 to 1 mm; and / or, The polishing pad includes the polishing layer, the buffer layer, the second adhesive layer and the release layer which are arranged in sequence.

9. The method for preparing the polishing pad according to any one of claims 4 to 8, comprising the steps of: providing the buffer layer; The polishing layer slurry is coated on the buffer layer to form the polishing layer.

10. Use of the polishing pad according to any one of claims 4 to 8 in chemical mechanical polishing.

Citation Information

Patent Citations

  • Polyvinyl alcohol-polyurethane elastic buffing wheel and preparation method thereof

    CN103395011A

  • Adsorption pad for fine grinding

    CN106985061A

  • Heat dissipation polishing pad and preparation method thereof

    CN116160355A

  • Polishing pad

    JP2004167680A

  • Porous chemical mechanical polishing pads

    US20170203406A1